ANALISIS PERILAKU PORTAL 3 DIMENSI PADA LEG SYSTEM TIPE JACKET TERHADAP BEBAN VERTIKAL MENGGUNAKAN METODE ELEMEN HINGGA DENGAN SAP2000 : Analisis Portal 3D pada Struktur Jacket - Sitti Suhaeni Sarhani Rahman; Rakhmat Alghifari Arif; Arsa Aldani Saptarina; Muhammad Zubair Muis Alie (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2026)
Jacket structures are a type of three-dimensional frame structure that is widely used in offshore structures to support vertical and lateral loads. Studies on the basic response of leg systems to pure vertical loads are important as a preliminary step before analyzing more complex environmental loads. This study aims to analyze the behavior of a three-dimensional portal structure on a jacket-type leg system using the SAP2000 finite element method. Modeling was performed on a 4-leg structure with diagonal and horizontal bracing using ASTM A992 steel cylindrical cross-sections. Vertical loads in the form of four concentrated loads of 1 kN each were applied to the top brace. The simulation results show a maximum displacement of Uz = 0.560 m, while the maximum lateral displacement is Ux/ Uy = 0.245 m. The maximum axial compressive force on the leg is 1059.44 kN, while the maximum tensile force is 7.41 kN. The maximum stress reaches 620.75 MPa on the center brace due to the concentration of stiffness and local moments. The maximum torsion of 3.42 kNm occurs as a result of the asymmetry of stiffness between elements. This study provides a basic understanding of global deformation, internal force distribution, and critical points of the jacket structure due to pure vertical loads and can be used as a basis for more complex analyses. Keywords: vertical load, structural deformation, FEM, jacket structure, SAP2000